Effectiveness of Health Communication via WhatsApp on Adolescents' Knowledge Change Regarding Gastritis Risk - Vannisa Rachmatika, Siti; Sumarti, Sri (Impact : Multidisciplinary Journal, 2025)
This study examines the effectiveness of using WhatsApp as a health communication tool to improve adolescents' knowledge about the risks of gastritis. Adolescents aged 15-18 years were provided with health messages via WhatsApp, focusing on the causes, symptoms, and prevention of gastritis. Using a qualitative approach, data were collected through in-depth interviews and documentation of WhatsApp conversations. The results revealed that adolescents had limited knowledge about gastritis prior to the intervention, often associating it solely with dietary habits. After receiving the health messages, there was a significant improvement in their understanding, particularly regarding the role of stress and the misuse of NSAIDs in triggering gastritis. WhatsApp’s interactive and multimedia features played a critical role in enhancing engagement and information retention. This study highlights the potential of WhatsApp as a scalable and effective platform for health education targeting adolescents. Future research should explore the use of other social media platforms in similar health communication interventions.